Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.

Red Flags in Torticollis: A Historical Cohort Study. - Starc, Meta; Norbedo, Stefania; Tubaro, Martina; Ronfani, Luca; Bassanese, Giulia; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: This study aimed to assess the spectrum of pathologies responsible for torticollis in children presenting to the emergency department and to evaluate the associated symptoms to determine clinical red flags for hospitalization. METHODS: This was a historical retrospective cohort study. Medical records of children evaluated in our emergency department for torticollis from 2008 to 2013 were reviewed. RESULTS: Among 392 identified patients, 61% had postural torticollis,19.4% infection related, 16.3% traumatic, and 3.5% other. Twenty-five patients (6.4%) were hospitalized. Four variables were strongly and independently related to the severe outcome: fever, sore throat, headache, and age. CONCLUSIONS: The association of 2 or 3 of these 4 features carried a risk of 32% and 58%, respectively, of having a severe illness.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Emergency Service, Hospital; Female; Hospitalization; Humans; Male; Retrospective Studies; Torticollis

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

Repositioning of Tak-475 In Mevalonate Kinase Disease: Translating Theory Into Practice. - Marcuzzi, Annalisa; Loganes, Claudia; Celeghini, Claudio; Kleiner, Giulio (Curr Med Chem, 2018)
BACKGROUND: Mevalonate Kinase Deficiency (MKD, OMIM #610377) is a rare autosomal recessive metabolic and inflammatory disease. In MKD, defective function of the enzyme mevalonate kinase, due to a mutation in the MVK gene, leads to the shortage of mevalonate- derived intermediates, which results in unbalanced prenylation of proteins and altered metabolism of sterols. These defects lead to a complex multisystem inflammatory and metabolic syndrome. OBJECTIVE: Although biologic therapies aimed at blocking the inflammatory cytokine interleukin- 1 can significantly reduce inflammation, they cannot completely control the clinical symptoms that affect the nervous system. For this reason, MKD can still be considered an orphan drug disease. The availability of MKD models reproducing the MKD-systematic inflammation, is crucial to improve the knowledge on its pathogenesis, which is still unknown. New therapies are also required in order to improve pateints' conditions and their quality of life. METHODS: MKD-cellular models can be obtained by biochemical inhibition of mevalonatederived isoprenoids. Of note, these cells present an exaggerated response to inflammatory stimuli that can be reduced by treatment with zaragozic acid, an inhibitor of squalene synthase, thus increasing the availability of isoprenoids intermediates upstream the enzymatic block. RESULTS: A similar action might be obtained by lapaquistat acetate (TAK-475, Takeda), a drug that underwent extensive clinical trials as a cholesterol lowering agent 10 years ago, with a good safety profile. CONCLUSIONS: Here we describe the preclinical evidence supporting the possible repositioning of TAK-475 from its originally intended use to the treatment of MKD and discuss its potential to modulate the mevalonate pathway in inflammatory diseases.
Keywords: Acyl Coenzyme A; Cholesterol; Drug Repositioning; Farnesyl-Diphosphate Farnesyltransferase; Humans; Hypercholesterolemia; Mevalonate Kinase Deficiency; Oxazepines; Phosphotransferases (Alcohol Group Acceptor); Piperidines

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Rothmund-Thomson Syndrome: Insights from New Patients on the Genetic Variability Underpinning Clinical Presentation and Cancer Outcome. - Colombo, Elisa A; Locatelli, Andrea; Cubells Sánchez, Laura; Romeo, Sara; Elcioglu, Nursel H; Maystadt, Isabelle; Esteve Martínez, Altea; Sironi, Alessandra; Fontana, Laura; Finelli, Palma; Gervasini, Cristina; Pecile, Vanna; et al. (Int J Mol Sci, 2018)
Biallelic mutations in gene, a caretaker of the genome, cause Rothmund-Thomson type-II syndrome (RTS-II) and confer increased cancer risk if they damage the helicase domain. We describe five families exemplifying clinical and allelic heterogeneity of RTS-II, and report the effect of pathogenic variants by predictions and transcripts analyses. Complete phenotype of patients #39 and #42 whose affected siblings developed osteosarcoma correlates with their c.[1048_1049del], c.[1878+32_1878+55del] and c.[1568G>C;1573delT], c.[3021_3022del] variants which damage the helicase domain. Literature survey highlights enrichment of these variants affecting the helicase domain in patients with cancer outcome raising the issue of strict oncological surveillance. Conversely, patients #29 and #19 have a mild phenotype and carry, respectively, the unreported homozygous c.3265G>T and c.3054A>G variants, both sparing the helicase domain. Finally, despite matching several criteria for RTS clinical diagnosis, patient #38 is heterozygous for c.2412_2414del; no pathogenic CNVs out of those evidenced by high-resolution CGH-array, emerged as contributors to her phenotype.
Keywords: Adolescent; Adult; Cell Line, Tumor; Child; Female; Homozygote; Humans; Male; Mutation; Pedigree; Phenotype; RecQ Helicases; Rothmund-Thomson Syndrome

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome

Review on the role of the human Polyomavirus JC in the development of tumors. - Delbue, Serena; Comar, Manola; Ferrante, Pasquale (Infect Agent Cancer, 2017)
Almost one fifth of human cancers worldwide are associated with infectious agents, either bacteria or viruses, and this makes the possible association between infections and tumors a relevant research issue. We focused our attention on the human Polyomavirus JC (JCPyV), that is a small, naked DNA virus, belonging to the family. It is the recognized etiological agent of the Progressive Multifocal Leukoencephalopathy (PML), a fatal demyelinating disease, occurring in immunosuppressed individuals. JCPyV is able to induce cell transformation in vitro when infecting non-permissive cells, that do not support viral replication and JCPyV inoculation into small animal models and non human primates drives to tumor formation. The molecular mechanisms involved in JCPyV oncogenesis have been extensively studied: the main oncogenic viral protein is the large tumor antigen (T-Ag), that is able to bind, among other cellular factors, both Retinoblastoma protein (pRb) and p53 and to dysregulate the cell cycle, but also the early proteins small tumor antigen (t-Ag) and Agnoprotein appear to cooperate in the process of cell transformation. Consequently, it is not surprising that JCPyV genomic sequences and protein expression have been detected in Central Nervous System (CNS) tumors and colon cancer and an association between this virus and several brain and non CNS-tumors has been proposed. However, the significances of these findings are under debate because there is still insufficient evidence of a casual association between JCPyV and solid cancer development. In this paper we summarized and critically analyzed the published literature, in order to describe the current knowledge on the possible role of JCPyV in the development of human tumors.

Risk of hospitalisation after early-revisit in the emergency department. - Cozzi, Giorgio; Ghirardo, Sergio; Fiorese, Ilaria; Proietti, Ilaria; Monasta, Lorenzo; Minute, Marta; Barbi, Egidio; Calligaris, Lorenzo (J Paediatr Child Health, 2017)
AIM: Early-revisits are frequent in the paediatric emergency department (ED) setting, but few data are available about early-revisited patients. The aim of this study was to investigate the hospitalisation rate of a population of early-revisited patients and to detect if an early-revisited patient was at risk of a more severe disease. METHODS: Between June 2014 and January 2015, we conducted a retrospective cohort study, considering all patients presented to the ED of a tertiary level children's hospital in Italy. We selected all patients who were revisited within 72 h from the initial visit (study cohort), while all other patients accessed in the same period were considered the control cohort. The two cohorts were compared for age, gender, triage category, hospitalisation rate, diagnosis at admission and hospital length of stay. RESULTS: In the study period, we reviewed 10 750 visits, of which 430 (4%) were unplanned revisits for the same chief complaint within 72 h from the initial visit. Hospitalisation rate of early-revisited patients was significantly higher compared to control patients (8.4 vs. 2.9%). Hospitalisation rate increases in parallel with the number of revisits, but in many cases, it was not directly related to a worst triage category, neither to a longer hospital length of stay. CONCLUSION: Early revisited patients in the ED had a significantly higher risk of hospitalisation, but this risk was only partially related to their clinical conditions.
Keywords: Adolescent; Child; Child, Preschool; Emergency Service, Hospital; Female; Hospitalization; Humans; Infant; Italy; Male; Retrospective Studies; Risk Assessment; Tertiary Care Centers; Time Factors

Recent advances in the use of Anti-TNFα therapy for the treatment of juvenile idiopathic arthritis. - Taddio, Andrea; Cattalini, Marco; Simonini, Gabriele; Cimaz, Rolando (Expert Rev Clin Immunol, 2016)
Juvenile Idiopathic Arthritis (JIA) encompasses a group of diseases of unknown etiology having in common arthritis in at least 1 joint that persists for 6 weeks and begins before 16 years of age, with other conditions excluded. With a prevalence of 1 per 1,000 children in the USA, JIA is the most common pediatric rheumatic illness and a major cause of acquired childhood disability. During the last 20 years, the advent of host immune response modifiers known as biologic agents, in particular the anti-TNFα agents (etanercept, infliximab, adalimumab), which directly inhibit the action of pro-inflammatory mediators, has revolutionized the treatment and the expected outcome of JIA. This article highlights treatment indications of anti-TNFα drugs and their more frequent side effects in JIA patients.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Resistance (R) Genes: Applications and Prospects for Plant Biotechnology and Breeding. - Pandolfi, Valesca; Neto, José Ribamar Costa Ferreira; Silva, Manassés Daniel; Amorim, Lidiane Lindinalva Barbosa; Wanderley-Nogueira, Ana Carolina; de Oliveira Silva, Roberta Lane; Kido, Éderson Akio; Crovella, Sergio; Iseppon, Ana Maria Benko (Curr Protein Pept Sci, 2016)
The discovery of novel plant resistance (R) genes (including their homologs and analogs) opened interesting possibilities for controlling plant diseases caused by several pathogens. However, due to environmental pressure and high selection operated by pathogens, several crop plants have lost specificity, broad-spectrum or durability of resistance. On the other hand, the advances in plant genome sequencing and biotechnological approaches, combined with the increasing knowledge on R-genes have provided new insights on their applications for plant genetic breeding, allowing the identification and implementation of novel and efficient strategies that enhance or optimize their use for efficiently controlling plant diseases. The present review focuses on main perspectives of application of R-genes and its co-players for the acquisition of resistance to pathogens in cultivated plants, with emphasis on biotechnological inferences, including transgenesis, cisgenesis, directed mutagenesis and gene editing, with examples of success and challenges to be faced.

Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. - Pontillo, A; Bricher, P; Leal, V N C; Lima, S; Souza, P R E; Crovella, S (J Med Virol, 2016)
PROBLEM: Only a small proportion of HPV+ women develop virus-associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. PATIENTS AND METHODS: 12 SNPs in seven inflammasome-related genes (NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. RESULTS: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high-risk HPV. CONCLUSION: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646-1651, 2016. © 2016 Wiley Periodicals, Inc.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

A rapid screening of ancestry for genetic association studies in an admixed population from Pernambuco, Brazil. - Coelho, A V C; Moura, R R; Cavalcanti, C A J; Guimarães, R L; Sandrin-Garcia, P; Crovella, S; Brandão, L A C (Genet Mol Res, 2015)
Genetic association studies determine how genes influence traits. However, non-detected population substructure may bias the analysis, resulting in spurious results. One method to detect substructure is to genotype ancestry informative markers (AIMs) besides the candidate variants, quantifying how much ancestral populations contribute to the samples' genetic background. The present study aimed to use a minimum quantity of markers, while retaining full potential to estimate ancestries. We tested the feasibility of a subset of the 12 most informative markers from a previously established study to estimate influence from three ancestral populations: European, African and Amerindian. The results showed that in a sample with a diverse ethnicity (N = 822) derived from 1000 Genomes database, the 12 AIMs had the same capacity to estimate ancestries when compared to the original set of 128 AIMs, since estimates from the two panels were closely correlated. Thus, these 12 SNPs were used to estimate ancestry in a new sample (N = 192) from an admixed population in Recife, Northeast Brazil. The ancestry estimates from Recife subjects were in accordance with previous studies, showing that Northeastern Brazilian populations show great influence from European ancestry (59.7%), followed by African (23.0%) and Amerindian (17.3%) ancestries. Ethnicity self-classification according to skin-color was confirmed to be a poor indicator of population substructure in Brazilians, since ancestry estimates overlapped between classifications. Thus, our streamlined panel of 12 markers may substitute panels with more markers, while retaining the capacity to control for population substructure and admixture, thereby reducing sample processing time.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

RelB activation in anti-inflammatory decidual endothelial cells: a master plan to avoid pregnancy failure? - Masat, Elisa; Gasparini, Chiara; Agostinis, Chiara; Bossi, Fleur; Radillo, Oriano; De Seta, Francesco; Tamassia, Nicola; Cassatella, Marco A; Bulla, Roberta (Sci Rep, 2015)
It is known that excessive inflammation at fetal-maternal interface is a key contributor in a compromised pregnancy. Female genital tract is constantly in contact with microorganisms and several strategies must be adopted to avoid pregnancy failure. Decidual endothelial cells (DECs) lining decidual microvascular vessels are the first cells that interact with pro-inflammatory stimuli released into the environment by microorganisms derived from gestational tissues or systemic circulation. Here, we show that DECs are hypo-responsive to LPS stimulation in terms of IL-6, CXCL8 and CCL2 production. Our results demonstrate that DECs express low levels of TLR4 and are characterized by a strong constitutive activation of the non-canonical NF-κB pathway and a low responsiveness of the canonical pathway to LPS. In conclusion, DECs show a unique hypo-responsive phenotype to the pro-inflammatory stimulus LPS in order to control the inflammatory response at feto-maternal interface.

Relevance of random biopsy at the transformation zone when colposcopy is negative. - Wiesenfeld, Uri; Mangino, Francesco Paolo; Toffoletti, Franco Giovanni; Ricci, Giuseppe (Obstet Gynecol, 2015)
Keywords: Cervical Intraepithelial Neoplasia; Colposcopy; Early Detection of Cancer; Female; Humans; Papillomavirus Infections; Precancerous Conditions; Uterine Cervical Neoplasms

Reply to Thalidomide Treatment of Pediatric Ulcerative Colitis: A New Use for an Old Drug. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2015)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Risk factors for mortality from acute lower respiratory infections (ALRI) in children under five years of age in low and middle-income countries: a systematic review and meta-analysis of observational studies. - Sonego, Michela; Pellegrin, Maria Chiara; Becker, Genevieve; Lazzerini, Marzia (PLoS One, 2015)
OBJECTIVE: To evaluate risk factors for death from acute lower respiratory infections (ALRI) in children in low- and middle-income countries. DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on risk factors for death from ALRI in children below five years in low- and middle income countries. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to January 2014. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 10,655 papers retrieved, 77 studies from 39 countries (198,359 children) met the inclusion criteria. Host and disease characteristics more strongly associated with ALRI mortality were: diagnosis of very severe pneumonia as per WHO definition (odds ratio 9.42, 95% confidence interval 6.37‒13.92); age below two months (5.22, 1.70‒16.03); diagnosis of Pneumocystis Carinii (4.79, 2.67‒8.61), chronic underlying diseases (4.76, 3.27‒6.93); HIV/AIDS (4.68, 3.72‒5.90); and severe malnutrition (OR 4.27, 3.47‒5.25). Socio-economic and environmental factors significantly associated with increased odds of death from ALRI were: young maternal age (1.84, 1.03‒3.31); low maternal education (1.43, 1.13‒1.82); low socio-economic status (1.62, 1.32‒2.00); second-hand smoke exposure (1.52, 1.20 to 1.93); indoor air pollution (3.02, 2.11‒4.31). Immunisation (0.46, 0.36‒0.58) and good antenatal practices (0.50, 0.31‒0.81) were associated with decreased odds of death. CONCLUSIONS: Host and disease characteristics as well as socio-economic and environmental determinants affect the risk of death from ALRI in children. Together with the prevention and treatment of chronic diseases, interventions to modify underlying risk factors such as poverty, lack of female education, and poor environmental conditions, should be considered among the strategies to reduce ALRI mortality in children in low- and middle-income countries.
Keywords: Child, Preschool; Developing Countries; Environmental Exposure; Humans; Infant; Infant, Newborn; Observational Studies as Topic; Poverty; Respiratory Tract Infections; Risk Factors; Survival Analysis

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Role of Pharmacogenetics in Hematopoietic Stem Cell Transplantation Outcome in Children. - Franca, Raffaella; Stocco, Gabriele; Favretto, Diego; Giurici, Nagua; Decorti, Giuliana; Rabusin, Marco (Int J Mol Sci, 2015)
Hematopoietic stem cell transplantation (HSCT) is an established therapeutic procedure for several congenital and acquired disorders, both malignant and nonmalignant. Despite the great improvements in HSCT clinical practices over the last few decades, complications, such as graft vs. host disease (GVHD) and sinusoidal obstructive syndrome (SOS), are still largely unpredictable and remain the major causes of morbidity and mortality. Both donor and patient genetic background might influence the success of bone marrow transplantation and could at least partially explain the inter-individual variability in HSCT outcome. This review summarizes some of the recent studies on candidate gene polymorphisms in HSCT, with particular reference to pediatric cohorts. The interest is especially focused on pharmacogenetic variants affecting myeloablative and immunosuppressive drugs, although genetic traits involved in SOS susceptibility and transplant-related mortality are also reviewed.

Romiplostim for secondary thrombocytopenia following allogeneic stem cell transplantation in children. - Maximova, Natalia; Zanon, D; Rovere, F; Maestro, A; Schillani, G; Paparazzo, R (Int J Hematol, 2015)
The outcome of romiplostim for secondary failure of platelet recovery (SFPR) was investigated in children who had undergone hematopoietic stem cell transplantation (HSCT). Seven transfusion-dependent pediatric patients (median age 11 years), with platelet counts below 10 × 10(9)/L, received four weekly doses of subcutaneous romiplostim to treat SFPR developed after HSCT. All patients, except one (patient 4), became platelet transfusion-independent in the second week from the beginning of treatment and no patient needed to discontinue drug treatment because of adverse events. Romiplostim could represent a beneficial first-line treatment, but further studies are required.

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Re: Tramadol can selectively manage moderate pain in children following European advice limiting codeine use. - Calligaris, Lorenzo; Marzuillo, Pierluigi; Barbi, Egidio (Acta Paediatr, 2014)

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

Risk of Essure microinsert abdominal migration: case report and review of literature. - Ricci, Giuseppe; Restaino, Stefano; Di Lorenzo, Giovanni; Fanfani, Francesco; Scrimin, Federica; Mangino, Francesco P (Ther Clin Risk Manag, 2014)
PURPOSE: To report a case of Essure microinsert abdominal migration and literature review. METHODS: A 41-year-old woman was counseled to undergo Essure sterilization. The procedure was hampered by the presence of endometrial cavity adhesions, obscuring left tubal ostium. By using microscissors the adhesions were progressively lysed. Since the procedure had become very painful, the patient required general anesthesia. Once adhesion lysis was completed, the tubal ostium was well visible. Both devices were then easily introduced into the fallopian tubes. At the end of the procedure, five coils were visible on the right side and five coils on the left side, as recommended. RESULTS: The 3-month hysterosalpingogram follow-up suspected abdominal migration of the left device. Laparoscopy confirmed the device displacement in the left lower abdominal quadrant. Both fallopian tubes and the uterus appeared normal. No signs of perforation were detected. The device was embedded into the omentum, but it was easily removed. Bilateral tubal sterilization was performed by bipolar coagulation. CONCLUSION: There are only 13 cases, including the present, of Essure abdominal migration in the literature. In most cases, abdominal displacement of the microinsert is asymptomatic and does not induce tissue damage. However, in some cases, it may cause a severe adverse event, requiring major surgery. Therefore, removal of the migrated device should be performed as soon as possible. Moreover, during presterilization counseling, the patient should also be correctly informed about the risk of this rare but relevant complication, as well as about the surgical interventions that could be required to solve it.

Rituximab in steroid-dependent or frequently relapsing idiopathic nephrotic syndrome. - Ruggenenti, Piero; Ruggiero, Barbara; Cravedi, Paolo; Vivarelli, Marina; Massella, Laura; Marasà, Maddalena; Chianca, Antonietta; Rubis, Nadia; Ene-Iordache, Bogdan; Rudnicki, Michael; Pollastro, Rosa Maria; Capasso, Giovambattista; et al. (J Am Soc Nephrol, 2014)
The outcome of steroid-dependent or frequently relapsing nephrotic syndrome of minimal change disease (MCD), mesangial proliferative GN (MesGN), or FSGS may be poor and with major treatment toxicity. This academic, multicenter, off-on trial (ClinicalTrials.gov #NCT00981838) primarily evaluated the effects of rituximab therapy followed by immunosuppression withdrawal on disease recurrence in 10 children and 20 adults with MCD/MesGN (n=22) or FSGS who had suffered ≥2 recurrences over the previous year and were in steroid-induced remission for ≥1 month. Participants received one dose (n=28) or two doses of rituximab (375 mg/m(2) intravenously). At 1 year, all patients were in remission: 18 were treatment-free and 15 never relapsed. Compared with the year before rituximab treatment, total relapses decreased from 88 to 22 and the per-patient median number of relapses decreased from 2.5 (interquartile range [IQR], 2-4) to 0.5 (IQR, 0-1; P<0.001) during 1 year of follow-up. Reduction was significant across subgroups (children, adults, MCD/MesGN, and FSGS; P<0.01). After rituximab, the per-patient steroid maintenance median dose decreased from 0.27 mg/kg (IQR, 0.19-0.60) to 0 mg/kg (IQR, 0-0.23) (P<0.001), and the median cumulative dose to achieve relapse remission decreased from 19.5 mg/kg (IQR, 13.0-29.2) to 0.5 mg/kg (IQR, 0-9.4) (P<0.001). Furthermore, the mean estimated GFR increased from 111.3±25.7 to 121.8±29.2 ml/min per 1.73 m(2) (P=0.01), with the largest increases in children and in FSGS subgroups. The mean height z score slope stabilized in children (P<0.01). Treatment was well tolerated. Rituximab effectively and safely prevented recurrences and reduced the need for immunosuppression in steroid-dependent or frequently relapsing nephrotic syndrome, and halted disease-associated growth deficit in children.
Keywords: Adolescent; Adrenal Cortex Hormones; Adult; Antibodies, Monoclonal, Murine-Derived; Child; Female; Glomerulonephritis, Membranoproliferative; Glomerulosclerosis, Focal Segmental; Humans; Male; Middle Aged; Nephrosis, Lipoid; Nephrotic Syndrome; Recurrence; Rituximab

The role of gestational diabetes, pre-pregnancy body mass index and gestational weight gain on the risk of newborn macrosomia: results from a prospective multicentre study. - Alberico, Salvatore; Montico, Marcella; Barresi, Valentina; Monasta, Lorenzo; Businelli, Caterina; Soini, Valentina; Erenbourg, Anna; Ronfani, Luca; Maso, Gianpaolo (BMC Pregnancy Childbirth, 2014)
BACKGROUND: It is crucial to identify in large population samples the most important determinants of excessive fetal growth. The aim of the study was to evaluate the independent role of pre-pregnancy body mass index (BMI), gestational weight gain and gestational diabetes on the risk of macrosomia. METHODS: A prospective study collected data on mode of delivery and maternal/neonatal outcomes in eleven Hospitals in Italy. Multiple pregnancies and preterm deliveries were excluded. The sample included 14109 women with complete records. Associations between exposure variables and newborn macrosomia were analyzed using Pearson's chi squared test. Multiple logistic regression models were built to assess the independent association between potential predictors and macrosomia. RESULTS: Maternal obesity (adjusted OR 1.7, 95% CI 1.4-2.2), excessive gestational weight gain (adjusted OR 1.9, 95% CI 1.6-2.2) and diabetes (adjusted OR 2.1, 95% CI 1.5-3.0 for gestational; adjusted OR 3.0, 95% CI 1.2-7.6 for pre-gestational) resulted to be independent predictors of macrosomia, when adjusted for other recognized risk factors. Since no significant interaction was found between pre-gestational BMI and gestational weight gain, excessive weight gain should be considered an independent risk factor for macrosomia. In the sub-group of women affected by gestational or pre-gestational diabetes, pre-gestational BMI was not significantly associated to macrosomia, while excessive pregnancy weight gain, maternal height and gestational age at delivery were significantly associated. In this sub-population, pregnancy weight gain less than recommended was not significantly associated to a reduction in macrosomia. CONCLUSIONS: Our findings indicate that maternal obesity, gestational weight gain excess and diabetes should be considered as independent risk factors for newborn macrosomia. To adequately evaluate the clinical evolution of pregnancy all three variables need to be carefully assessed and monitored.
Keywords: Adolescent; Adult; Birth Weight; Body Height; Body Mass Index; Diabetes, Gestational; Female; Fetal Macrosomia; Gestational Age; Humans; Infant, Newborn; Italy; Middle Aged; Obesity; Pregnancy; Pregnancy in Diabetics; Prospective Studies; Risk Factors; Weight Gain; Young Adult

A real-time polymerase chain reaction-based protocol for low/medium-throughput Y-chromosome microdeletions analysis. - Segat, Ludovica; Padovan, Lara; Doc, Darja; Petix, Vincenzo; Morgutti, Marcello; Crovella, Sergio; Ricci, Giuseppe (Genet Test Mol Biomarkers, 2012)
PURPOSE: We describe a real-time polymerase chain reaction (PCR) protocol based on the fluorescent molecule SYBR Green chemistry, for a low- to medium-throughput analysis of Y-chromosome microdeletions, optimized according to the European guidelines and aimed at making the protocol faster, avoiding post-PCR processing, and simplifying the results interpretation. METHODS: We screened 156 men from the Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy), 150 not presenting Y-chromosome microdeletion, and 6 with microdeletions in different azoospermic factor (AZF) regions. For each sample, the Zinc finger Y-chromosomal protein (ZFY), sex-determining region Y (SRY), sY84, sY86, sY127, sY134, sY254, and sY255 loci were analyzed by performing one reaction for each locus. RESULTS: AZF microdeletions were successfully detected in six individuals, confirming the results obtained with commercial kits. CONCLUSION: Our real-time PCR protocol proved to be a rapid, safe, and relatively cheap method that was suitable for a low- to medium-throughput diagnosis of Y-chromosome microdeletion, which allows an analysis of approximately 10 samples (with the addition of positive and negative controls) in a 96-well plate format, or approximately 46 samples in a 384-well plate for all markers simultaneously, in less than 2 h without the need of post-PCR manipulation.
Keywords: Azoospermia; Chromosome Deletion; Chromosomes, Human, Y; Female; Humans; Kruppel-Like Transcription Factors; Male; Real-Time Polymerase Chain Reaction; Sex Chromosome Aberrations; Sex Chromosome Disorders of Sex Development

Recurrent fever and fitful abdominal pain in a child. - Zanchi, Chiara; Paloni, Giulia; Marchetti, Federico (Gastroenterology, 2012)
Keywords: Abdominal Pain; Child; Female; Fever; Giant Lymph Node Hyperplasia; Humans; Recurrence

A red baby should not be taken too lightly. - Faletra, Flavio; Bruno, Irene; Berti, Irene; Pastore, Serena; Pirrone, Angela; Tommasini, Alberto (Acta Paediatr, 2012)
AIM: To identify clinical and laboratory features that can drive the differential diagnosis of a primary immunodeficiency diseases in patients with ectodermal defects. METHODS: Analysis of selected teaching cases. RESULTS: We identified four exemplary cases that allowed to point out specific clues. CONCLUSIONS: A careful evaluation of immune and ectodermal signs is the key to the diagnosis. Therefore, a multidisciplinary approach can lead to diagnosis and to an appropriate treatment in most of the cases.
Keywords: Child, Preschool; Dermatitis; Ectodermal Dysplasia; Female; Humans; Immunologic Deficiency Syndromes; Infant; Male; Netherton Syndrome; Severe Combined Immunodeficiency; Skin

Relation between maternal thrombophilia and stillbirth according to causes/associated conditions of death. - Monari, F; Alberico, S; Avagliano, L; Cetin, I; Cozzolino, S; Gargano, G; Marozio, L; Mecacci, F; Neri, I; Tranquilli, A L; Venturini, P; Facchinetti, F (Early Hum Dev, 2012)
OBJECTIVE: To investigate maternal thrombophilia in cases of Stillbirth (SB), also an uncertain topic because most case series were not characterised for cause/associated conditions of death. STUDY DESIGN: In a consecutive, prospective, multicentre design, maternal DNA was obtained in 171 cases of antenatal SB and 326 controls (uneventful pregnancy at term, 1:2 ratio). Diagnostic work-up of SB included obstetric history, neonatologist inspection, placenta histology, autopsy, microbiology/chromosome evaluations. Results audited in each centre were classified by two of us by using CoDAC. Cases were subdivided into explained SB where a cause of death was identified and although no defined cause was detected in the remnants, 64 cases found conditions associated with placenta-vascular disorders (including preeclampsia, growth restriction and placenta abruption - PVD). In the remnant 79 cases, no cause of death or associated condition was found. Antithrombin activity, Factor V Leiden, G20210A Prothrombin mutation (FII mutation) and acquired thrombophilia were analysed. RESULTS: Overall, the presence of a thrombophilic defect was significantly more prevalent in mothers with SBs compared to controls. In particular, SB mothers showed an increased risk of carrying Factor II mutation (OR=3.2, 95% CI: 1.3-8.3, p=0.01), namely in unexplained cases. Such mutation was significantly associated also with previous SB (OR=8.9, 95%CI 1.2-70.5). At multiple logistic regression, Factor II mutation was the only significantly associated variable with SB (adj OR=3.8, 95% CI: 1.3-13.5). CONCLUSION: These data suggest that Factor II mutation is the only condition specifically associated with unexplained SB and could represents a risk of recurrence. PVD-associated condition is unrelated to thrombophilia.
Keywords: Adult; Case-Control Studies; Cause of Death; Female; Fetal Diseases; Fetal Mortality; Humans; Infant, Newborn; Male; Placenta Diseases; Pre-Eclampsia; Pregnancy; Pregnancy Complications, Hematologic; Socioeconomic Factors; Stillbirth; Thrombophilia; Young Adult

Review of the scientific literature on the health of the Roma and Sinti in Italy. - Monasta, Lorenzo; Erenbourg, Anna; Restaino, Stefano; Lutje, Vittoria; Ronfani, Luca (Ethn Dis, 2012)
BACKGROUND: Roma and Sinti in Italy are excluded from the rest of society, often live in precarious housing conditions and have poor access to health services. In Italy, the Roma and Sinti minority (.3% of the overall population) is scarcely represented if compared with other European countries. METHODS: To establish what is known and how Roma and Sinti health is studied in Italy, we conducted a review of the scientific literature, including articles published between 2000 and 2010, found in Medline, Embase and Web of Science. RESULTS: We analyzed 15 relevant articles out of 32 references. Four papers describe rare autosomal recessive disorders. Four illustrate outbreaks of measles. The remaining papers describe health conditions suffered by this minority. All but two, however, are based on data collected at health services. CONCLUSIONS: The lack of prevalence data and analysis of determinants is a detriment to the health of the Roma and Sinti populations in Italy. Participatory research and evidence-based interventions are needed to improve health outcomes and living conditions of the Roma and Sinti people.
Keywords: Gypsies; Health Services Accessibility; Health Status; Housing; Humans; Italy; Minority Groups; Prejudice

RICH (rapidly involuting congenital hemangioma): not only a definition of wealth. - Abate, Maria Valentina; Davanzo, Riccardo; Bibalo, Chiara; Zennaro, Floriana; Berti, Irene (J Pediatr, 2012)
Keywords: Female; Hemangioma; Humans; Infant, Newborn; Skin Neoplasms

Role of high molecular weight hyaluronic acid in postmenopausal vaginal discomfort. - Grimaldi, E F; Restaino, S; Inglese, S; Foltran, L; Sorz, A; Di Lorenzo, G; Guaschino, S (Minerva Ginecol, 2012)
AIM: Aim of the present study was to quantify the intensity of vulvovaginal symptoms before and after treatment with high molecular weight hyaluronic acid (HA), to test the tolerability and safety of the product, to evaluate the effect on the quality of life and the compliance to the treatment. METHODS: This was a double-blind randomized placebo-controlled study. In seven months we enrolled 36 post-menopausal women, equally distributed in placebo and active group. The evaluation was based on at least three atrophy-related signs and on the patient reported symptoms. After the written informed consent, the participants were instructed to apply the gel (drug or placebo) daily. Three days after the end of the treatment the patients received a final examination to evaluate the progress of symptoms, the presence of any adverse events and their correlation with the treatment. RESULTS: Self-evaluation scales and investigator evaluation showed that the vaginal dryness was significantly reduced both in placebo and in the active group; however, high molecular weight HA was the only active treatment in reducing significantly itching and burning (P<0.02 and <0.04 respectively). Both treatments significantly reduced vaginal atrophy (P<0.001), erythema (P<0.01 placebo and P<0.001 HA) and vaginal dryness (P<0.001), but HA treatment was significantly more effective on the first two symptoms. Both treatments were very well tolerated and compliance of the treatment was very high. CONCLUSION: High molecular weight HA could be effective in subjective and objective improvement of postmenopausal vaginal atrophy providing a good compliance. No adverse events occurred during the entire period of the study.
Keywords: Atrophy; Double-Blind Method; Female; Humans; Hyaluronic Acid; Middle Aged; Molecular Weight; Postmenopause; Vagina; Vaginal Diseases

Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Recent advances in the understanding and management of MYH9-related inherited thrombocytopenias. - Balduini, Carlo L; Pecci, Alessandro; Savoia, Anna (Br J Haematol, 2011)
MYH9-related disease (MYH9-RD) is one of the most frequent forms of inherited thrombocytopenia. It is transmitted in an autosomal dominant fashion and derives from mutations of MYH9, the gene for the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia with mild bleeding tendency and may develop kidney dysfunction, deafness and cataracts later in life. The term MYH9-RD encompasses four autosomal-dominant thrombocytopenias that were previously described as distinct disorders, namely May-Hegglin Anomaly, Sebastian, Fechtner and Epstein syndromes. Thrombocytopenia is usually mild and derives from complex defects of megakaryocyte maturation and platelet formation. It is easily diagnosed, in that the presence of giant platelets in peripheral blood raises the suspicion of MYH9-RD and a simple immunofluorescence test on blood films confirms the diagnostic hypothesis. However, genotype/phenotype correlations have been recognized and mutation screening is therefore required to define the risk of acquiring extra-haematological defects. Results of a small clinical study suggested that a non-peptide thrombopoietin mimetic might greatly benefit both thrombocytopenia and bleeding tendency of MYH9-RD patients.
Keywords: Animals; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Humans; Mice; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Myosin Type II; Phenotype; Thrombocytopenia

Refractory iron-deficiency anaemia in a child with portal cavernoma. - Pastore, Serena; Londero, Margherita; Cont, Gabriele; Di Leo, Grazia; Ventura, Alessandro (Gut, 2011)
Keywords: Anemia, Iron-Deficiency; Antihypertensive Agents; Child; Hemangioma, Cavernous; Humans; Hypertension, Portal; Ileal Diseases; Male; Propranolol; Vascular Neoplasms

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

Role of DC-SIGN and L-SIGN receptors in HIV-1 vertical transmission. - da Silva, Ronaldo Celerino; Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
The innate immune system acts in the first line of host defense against pathogens. One of the mechanisms used involves the early recognition and uptake of microbes by host professional phagocytes, through pattern recognition receptors (PRRs). These PRRs bind to conserved microbial ligands expressed by pathogens and initiate both innate and adaptative immune responses. Some PRRs located on the surface of dendritic cells (DCs) and other cells seem to play an important role in human immunodeficiency virus type 1 (HIV-1) transmission. Dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin, CD209 (DC-SIGN) and its homolog, DC-SIGN-related (DC-SIGNR or L-SIGN) receptors are PPRs able to bind the HIV-1 gp120 envelope protein and, because alterations in their expression patterns also occur, they might play a role in both horizontal and vertical transmission as well as in disseminating the virus within the host. This review aims to explore the involvement of the DC-SIGN and L-SIGN receptors in HIV-1 transmission from mother to child.
Keywords: Cell Adhesion Molecules; HIV Infections; HIV-1; Humans; Immunity, Innate; Infectious Disease Transmission, Vertical; Lectins, C-Type; Polymorphism, Genetic; Receptors, Cell Surface

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella

Risk of preterm delivery in relation to maternal use of psychotropic medications during pregnancy: methodological issues. - Erenbourg, Anna; Wiesenfeld, Uri; Ronfani, Luca (Am J Obstet Gynecol, 2010)
Keywords: Benzodiazepines; Confounding Factors (Epidemiology); Data Interpretation, Statistical; Female; Humans; Multivariate Analysis; Pregnancy; Premature Birth; Psychotropic Drugs

Rotavirus vaccine efficacy in African and Asian countries. - Tamburlini, Giorgio; Cattaneo, Adriano; Monasta, Lorenzo (Lancet, 2010)
Keywords: Africa; Child; Dysentery; Gastroenteritis; Humans; Rotavirus Infections; Rotavirus Vaccines; Treatment Outcome

Radiochemical assay of glutathione S-epoxide transferase and its enhancement by phenobarbital in rat liver in vivo. - Marniemi, J; Parkki, M G (Biochem Pharmacol, 1975)
Keywords: Animals; Carrier Proteins; Epoxy Compounds; Glutathione; Glutathione Transferase; Hydrogen-Ion Concentration; Liver; Male; Methylcholanthrene; Phenobarbital; Rats; Stimulation, Chemical; Styrenes